2021
DOI: 10.1021/acsanm.1c01157
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Carbon Nanotube Structures with High Aspect Ratio Nanopores for Li-Ion Battery Anodes

Abstract: Technological advances in membrane technology, catalysis, and electrochemical energy storage require the fabrication of controlled pore structures at ever smaller length scales. It is therefore important to develop processes allowing for the fabrication of materials with controlled submicron porous structures. We propose a combination of colloidal lithography and chemical vapor deposition of carbon nanotubes to create continuous straight pores with diameters down to 100 nm in structures with thicknesses of mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…However, the surface adsorption of the guest H2 molecule is endothermic below 600 0 C and exothermic above 600 0 C, claim to this report are presented in Figure 7. This behavior can be connected to the small size of the SWCNT and the repulsion behaviors of electrons due to electron density of the SWCNT (Sarah et al, 2021) More and also dense states are seen in the valence band than in the conduction bands. Higher peak was also observed at energy level corresponding to -7 eV.…”
Section: Binding Energiesmentioning
confidence: 99%
“…However, the surface adsorption of the guest H2 molecule is endothermic below 600 0 C and exothermic above 600 0 C, claim to this report are presented in Figure 7. This behavior can be connected to the small size of the SWCNT and the repulsion behaviors of electrons due to electron density of the SWCNT (Sarah et al, 2021) More and also dense states are seen in the valence band than in the conduction bands. Higher peak was also observed at energy level corresponding to -7 eV.…”
Section: Binding Energiesmentioning
confidence: 99%
“…Several studies investigating CNTs as potential anodes materials have shown they have high storage capacities 132 . Importantly, both the intercalation of Li + on tube surface sites and within the central tube are directly influenced by CNT synthesis, process treatments, and surface modifications 82,133,134 . For instance, SWCNTs produced by laser evaporation were found to have storage capacities around 1050 mA h g −1 135 .…”
Section: Major Components Anode Cathode Electrolytes and Separatorsmentioning
confidence: 99%
“…132 Importantly, both the intercalation of Li + on tube surface sites and within the central tube are directly influenced by CNT synthesis, process treatments, and surface modifications. 82,133,134 For instance, SWCNTs produced by laser evaporation were found to have storage capacities around 1050 mA h g −1 . 135 Studies have also shown that hybrid anode materials composed of CNTs doped with nanostructured materials (like Ge, Sb, Sn, Si, etc.)…”
Section: Carbon Nanotube (Cnt)-based Anode Materialsmentioning
confidence: 99%
“…Since the discovery of carbon nanotubes (CNTs) in 1991, they have demonstrated tremendous potential in the fabrication of energy storage devices, including lithium‐based rechargeable batteries, due to their unique 1D nanostructure, low density, excellent electrical and mechanical properties, as well as preferable chemical and thermal stability. Atomically, CNTs are tubular nanomaterials (constructed by sp 2 bonded carbon atoms) with a high aspect ratio (≈10 3 ), [ 6 ] and the hollow voids of the graphitic layers arranged in the cylinder shape endow them with a low density (≈2 g cm −3 ). [ 7 ] It has been shown that the electrical conductivity of an individual CNT is dependent on both intrinsic factors (including the length, [ 8 ] diameter, [ 9 ] and chirality (for single‐wall carbon nanotubes, SWCNTs) [ 10 ] ) and external stimuli (such as the temperature change [ 11 ] and the applied pressure [ 12 ] ), with the measured resistivity of pristine CNTs measured to be ≈10 −5 Ω m. [ 13 ] Furthermore, CNTs are mechanically strong with the reported Young's modulus and tensile stress of an individual CNT in the range of TPa [ 14 ] and GPa, [ 15 ] respectively.…”
Section: Introductionmentioning
confidence: 99%